Comparison of Effects of Companionship During Labour on The Perception of Pain and Timely Initiation of Breast-Feeding - Niazi, Nayab Gul; Ali, Haider; Ayaz, Saeed Bin (Pakistan Armed Forces Medical Journal, 2022)
Objective: To compare the effect of companionship in labour in terms of pain reduction in the active phase of labour and timely initiation of breastfeeding. Study Design: Quasi-experimental study. Place and Duration of Study: Department of Obstetrics and Gynecology, Holy Family Hospital, from Jan to Jul 2016. Methodology: Sixty-two primigravida women with singleton pregnancy and cephalic presentation presenting in the active phase of labour were allocated randomly by lottery method into the intervention companion-group and the control group without a companion. The companion-group received standardized instructions. The pain during labour was measured using the numeric rating scale. Women were interviewed in the postnatal ward one hour after the delivery for timely breastfeeding initiation. Results: The mean age of the intervention and the control groups was approximately similar, i.e., 25 ± 3 years. The mean pain score in the intervention group (7.27 ± 1.06) was significantly lower than the mean pain score in the control group (8.21 ± 0.81) (p=0.038). Women in the intervention group had a significantly higher frequency of timely breastfeeding initiation than women in the control group (p=0.001). There was no significant difference in pain reduction based on the relationship of the companion. However, the frequency of timely breastfeeding initiation was significantly higher (p=0.02) when the companion was the mother of the parturient. Conclusion: The presence of a companion during labour decreases pain and increases the frequency of timely breastfeeding initiation compared to having no companion.